2001
DOI: 10.7153/mia-04-11
|View full text |Cite
|
Sign up to set email alerts
|

Weyl's Theorem for Class A Operators

Abstract: Abstract. In this paper, we show that Weyl's theorem holds for class A operators under a certain condition. We also show that a class A operator whose Weyl spectrum equals to the one-point set {0} is always compact and normal. (2000): 47A53, 47B20. Key words and phrases: Class A operators, w -hyponormal operators, continuity of spectra, Weyl's theorem. Mathematics subject classification R E F E R E N C E S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…In [14], W. Y. Lee and S. H. Lee showed that if T ∈ B(H) is a hyponormal operator and f ∈ H(σ(T )), then Weyl's theorem holds for f (T ). Recently, this result was extended to p-quasihyponormal operators, class A operators and quasi-class A operators in [19], [18] and [5], respectively. In this section we show that if T ∈ B(H) is a quasi-class (A, k) operator and f ∈ H(σ(T )), then Weyl theorem holds for f (T ).…”
Section: Following [3] We Say That T ∈ B(h) Satisfies Weyl's Theoremmentioning
confidence: 96%
See 1 more Smart Citation
“…In [14], W. Y. Lee and S. H. Lee showed that if T ∈ B(H) is a hyponormal operator and f ∈ H(σ(T )), then Weyl's theorem holds for f (T ). Recently, this result was extended to p-quasihyponormal operators, class A operators and quasi-class A operators in [19], [18] and [5], respectively. In this section we show that if T ∈ B(H) is a quasi-class (A, k) operator and f ∈ H(σ(T )), then Weyl theorem holds for f (T ).…”
Section: Following [3] We Say That T ∈ B(h) Satisfies Weyl's Theoremmentioning
confidence: 96%
“…In [14], W. Y. Lee and S. H. Lee showed that if T is hyponormal operator, then Weyl's theorem holds for f (T ), where f is an analytic function on a neighborhood of spectrum of T . Recently, this result was extended to p-quasihyponormal operators, class A operators and quasi-class A operators in [19], [18] and [5], respectively.…”
Section: Introductionmentioning
confidence: 96%
“…From these facts and Lemma 3.2. we have the following lemma. [8]) Let T be a paranormal operator and λ ∈ σ(T ) be an isolated point. Then the Riesz idempotent E with respect to λ defined by (1) satisfies ranE = ker(T − λ).…”
Section: Lemma 33 Let M Be An Invariant Subspace Of Paranormal Opermentioning
confidence: 99%
“…Berberian [6,7]. And this result was generalized for p-hyponormal operators by M. Chō, M. Iton and S.Ōshiro [9], for class A operators by A. Uchiyama [31], for algebraically hyponormal operators by Y.M. Han [22] and for algebraically paranormal operators by R.E.…”
Section: An Operator T ∈ B(h) Is Called Weyl If It Is Fredholm Of Indmentioning
confidence: 99%